Impact of Pediococcus acidilactici GLP06 supplementation on gut microbes and metabolites in adult beagles: a comparative analysis - Zhao, Mengdi; Zhang, Yuanyuan; Li, Yueyao; Liu, Keyuan; Bao, Kun; Li, Guangyu (Frontiers in Microbiology, 2024)
There is growing interest in the potential health benefits of probiotics for both humans and animals. The study aimed to investigate the effects of feeding the canine-derived probiotic Pediococcus acidilactici GLP06 to adult beagles by analysing the microbiome and metabolome. Twenty-four healthy adult beagles were randomly assigned to four groups. The CK group received a standard diet, while the three probiotic groups, the LG group (2×108 CFU/day/dog), MG group (2×109 CFU/day/dog), and HG group (2×1010 CFU/day/dog), received the standard diet supplemented with varying amounts of probiotics. The results show that, compared to the CK group, total antioxidant capacity was significantly increased in the MG and HG groups (P< 0.05) and superoxide dismutase and catalase were significantly increased in the HG group (P< 0.05). Compared to the CK group, malondialdehyde and blood urea nitrogen content were significantly decreased in the MG and HG groups (P< 0.05). Additionally, secretory immunoglobulin A activity was significantly increased in the HG group compared to the CK and LG groups (P< 0.05) and immunoglobulin G activity was significantly increased in the HG group compared to the CK, LG and MG groups (P< 0.05). In addition, compared with the CK group, the abundance of Faecalitalea and Collinsella increased in the LG group and the relative abundances of Tyzzerella and Parasutterella increased in the MG group. The α diversity and the relative abundances of beneficial bacteria (Faecalibacterium, Lachnospiraceae_NK4A1316, and Ruminococcaceae_UCG-005) were higher in the HG group than in the CK group. Furthermore, acetic acid content was significantly increased in the HG group compared to the CK, LG and MG groups (P< 0.05). The butyric acid, isobutyric acid and total SCFA content were significantly increased in the HG group compared to the CK group (P< 0.05). Moreover, metabolome analysis revealed 111 upregulated and 171 downregulated metabolites in the HG group. In conclusion, this study presents evidence that supplementing with P. acidilactici GLP06 can have a positive impact on antioxidant activity, immunoproteins, SCFAs and gut microbiota in adult beagle. These findings highlight the potential of probiotics as a dietary intervention to enhance gut health and overall well-being in companion animals.